Dynamics of spectral characteristics of EEG under induced stress of psychosocial genesis - Tolstoguzov N. Sergey; Savin R. Michael; Elifanov V. Andrey (Environment and Social Psychology, 2025)
The purpose of this work was to study the spectral characteristics of the EEG during induced stress of psychosocial origin in young people studying at a higher educational institution. In 40 subjects (19 men and 21 women), the indicators of the full power of the spectrum (μV2) in the given frequency ranges, the integral EEG alpha/theta indices for the power of the spectrum were studied using 16 standard leads, and the averaged indicators of the full power of the spectrum (μV2) in the frontal areas of the left (Fp1, F3, F7) and right (Fp2, F4, F8) hemispheres. According to the full spectrum power indicator, averaged over 16 active leads, an increase was noted in the Δ-, θ-, α- and β-ranges in the preparatory, reactive and cognitive stages of the stress reaction, which indicated the involvement of all oscillatory systems in the implementation of the stress response, regardless of their relationship with the brainstem, limbic (Δ- and θ-rhythms) or thalamocortical (α- and β-rhythms) structures. The alpha/theta index decreased according to the stages of the Trier test. Psychosocial reactivity in the slow-wave components (Δ- and θ-rhythms) of the power spectrum was more pronounced in men, while in the fast-wave components (β1- and β2-rhythms) - in women. No frontal asymmetry of the alpha rhythm was detected during the experiment.